2015
DOI: 10.1016/j.apcata.2015.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of bismuth–cerium-molybdate selective propylene ammoxidation catalysts

Abstract: a b s t r a c tAcrylonitrile is a major chemical intermediate used in the production of a wide range of chemical and polymer products. Central to the commercial process is a proprietary catalyst consisting of a complex mixture of metal oxides containing a bismuth-containing molybdate phase that is active and selective for propylene ammoxidation to acrylonitrile. Among the most active and selective is a solid solution of bismuth and cerium molybdate. Solid state structural studies were undertaken to characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…The pattern of the powders calcined at 800 ºC shows the diffraction peaks of the monoclinic phase, but it was also observed the appearance of Ce 11 O 20 and Ce 7 O 12 phases due to cerium oxidation. This result was also related by Brazdil et al (2015) 19 that demonstrated the appearance of CeO 2 phases in the synthesis of cerium molybdate at temperatures above 600 ºC. The diffractograms of the cerium molybdate powders were indexed with lanthanum molybdate cards, as they are isostructural and due to the unavailability of tetragonal and monoclinic cerium molybdate cards in the literature.…”
Section: Powder X-ray Diffractionmentioning
confidence: 97%
See 1 more Smart Citation
“…The pattern of the powders calcined at 800 ºC shows the diffraction peaks of the monoclinic phase, but it was also observed the appearance of Ce 11 O 20 and Ce 7 O 12 phases due to cerium oxidation. This result was also related by Brazdil et al (2015) 19 that demonstrated the appearance of CeO 2 phases in the synthesis of cerium molybdate at temperatures above 600 ºC. The diffractograms of the cerium molybdate powders were indexed with lanthanum molybdate cards, as they are isostructural and due to the unavailability of tetragonal and monoclinic cerium molybdate cards in the literature.…”
Section: Powder X-ray Diffractionmentioning
confidence: 97%
“…(28 º -34 º and 46 º -58 º), plus the weaker low-angle (10 º -25 º) superstructure diffraction peaks which are the fingerprints of the defect monoclinic phase 19 . The pattern of the powders calcined at 800 ºC shows the diffraction peaks of the monoclinic phase, but it was also observed the appearance of Ce 11 O 20 and Ce 7 O 12 phases due to cerium oxidation.…”
Section: Powder X-ray Diffractionmentioning
confidence: 99%
“…Bi 2 O 3 , a common oxide semiconductor, is widely used in the elds of chemical engineering and electronics such as NO detection 23 and the oxidation or ammoxidation of propylene. 24,25 In the oxidation/ammoxidation of propene over bismuth/ molybdate catalyst, bismuth was thought to involve the ratedetermining hydrogen abstraction from propylene, 26 exhibiting its mild oxidizing characteristics. This property might be also benecial for the partial oxidation of propylene in C 3 H 6 -SCR for NO reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Compounds with a Bi/Mo ratio of 3:1 was found to produce a α-Bi 2 Mo 3 O 12 compound exhibiting acrolein selectivity in the range of 36%-56%, providing a 60%-63% propylene conversion. Brazdil et al [14] reported on the synthesis of bismuth-cerium molybdate compounds with a Bi x Ce 2−x Mo 3 O 12 formulation. They studied the selectivity as a function of cerium content, to prove its effectiveness in reactions for catalytic propylene ammoxidation.…”
Section: Introductionmentioning
confidence: 99%